Psalmist's cry : scripts for embracing lament - Brueggemann, Walter (House Studio, 2010)
"In Psalmist's Cry, Walter Brueggemann explores Psalms as scripts for lament-guides for how to express feelings honestly, in ways normally not permitted or expected within the Christian community. In this 5-week study, discover the fullness of God when we allow our lives to become about him healing us and not about us controlling or managing our way through life." -- from book cover.